Rotavirus genomics. Public health impact - Susana López; Carlos F Arias (Instituto Nacional de Salud Pública, 2019)
With the introduction of rotavirus vaccines Rotarix (RV1) or RotaTeq (RV5) in the immunization programs of an increasing number of countries, there is concern that the immune selection pressure induced will cause an increase in the prevalence of virus genotypes not included in the vaccine formulation, or to the appearance of novel rotavirus strains that could evade the protective immune response. The natural fluctuation of rotaviruses makes it difficult to distinguish if the change in the circulating strains is due to the vaccine selective pressure or to the natural diversity fluctuation of viruses. If there has been a selective pressure, it has been low so far. However, it is important to keep an epidemiological surveillance and pay attention to the emergence of strains that are resistant to the vaccine, in particular in those countries where the viral diversity has been shown to be higher.